Konsep diri Menghadapi Intervensi dalam Cerpen Teken Pang Néken - Paramitha, Ni Made Ayu Susanthi Pradnya; Artayasa, I Wayan; Aditya, I Wayan Yus; Sari, Ni Kadek Puspita (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2024)
Short stories are a form of literary work that offers various kinds of life problems, as well as problems with humans and their humanity. The short story Teken Pang Neken appears as a literary work that describes a hidden phenomenon or perhaps actually open but considered hidden. Departing from this, the research will explore more deeply the main character's self-concept in dealing with various interventions that lead to him. The research was conducted using a qualitative descriptive method with a psycho-objective approach. Data was collected using literature study using note-taking techniques and then analyzed using Rogers' personality theory and Higgins' discrepancy theory. The research results are described based on the dimensions of knowledge, hope and self-assessment of Ngurah Toni as the main character. Knowledge of oneself is reflected in the name and position of the equipment being held. Hope refers to the safe position that one aspires to as the ideal self in the future. Firmness in maintaining integrity amidst the onslaught of intervention gave rise to a positive assessment of Ngurah Toni.